Audiovisual journalism and technological innovation: The QR codes on Spanish television - Cartes-Barroso, Manuel Jesús (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This article analyses the presence of QR codes in Spanish television news programmes, as well as their use and characteristics. The methodology used is the content analysis of the news programmes of Antena 3, La Sexta, La 1 and Telecinco. Among the results obtained in this article, it is confirmed that QR codes are still underdeveloped in these programmes, because its use is variable, they are not implemented in all channels and they act mostly as another decorative element that appears on the television screen.